Raised concentration of plasma creatine kinase BB isoenzyme in myelodysplasia. Issue 6 (June 1994) - Crook, M; Williams, A; Sankaralingam, A; Tutt, P
Abstract : A 72 year old woman presented with a suspected myocardial infarction. An echocardiograph showed no acute changes but her plasma creatine kinase (CK) activity was increased at 343 U/l (< 175 normal range). The apparent creatine kinase-MB activity by a CK-M subunit immunoinhibition assay was 350 U/l. In view of the discrepancy between the total creatine kinase and CK-MB activity plasma creatine kinase electrophoresis studies were performed which showed not only a band of creatine kinase-MM but also a band of creatine kinase-BB, 53% of the total creatine kinase activity. No band of CK-MB was seen. It later transpired that the woman had myelodysplasia. It is suggested that premalignant and malignant haematological conditions should be considered in patients with an unexplained increase in plasma CK-BB.